Integration of Cot Inverse x

Here you will learn proof of integration of cot inverse x or arccot x and examples based on it.

Let’s begin –

Integration of Cot Inverse x

The integration of cot inverse x or arccot x is \(xcot^{-1}x\) + \(1\over 2\) \(log |1 + x^2|\) + C

Where C is the integration constant.

i.e. \(\int\) \(cot^{-1}x\) = \(xcot^{-1}x\) – \(1\over 2\) \(log |1 + x^2|\) + C

Proof : 

We have, I = \(\int\) \(cot^{-1}x\) dx

Let \(cot^{-1}x\) = t,

Then, x = cot t

\(\implies\) dx = d(cot t) = \(-cosec^2 t\) dt

\(\therefore\) I = \(\int\) \(cot^{-1}x\) dx

\(\implies\) I = \(\int\) t \(-cosec^2 t\) dt

By using integration by parts formula,

I = t cot t – \(\int\) 1. (cot t) dt

I = t cot t – log |sin t| + C

Since cot t = x \(\implies\) cosec t = \(\sqrt{1 + cot^2 t}\) = \(\sqrt{1 + x^2}\)

Hence, sin t = \(1\over \sqrt{1 + x^2}\)

Now, Put t = \(cot^{-1}x\) here,

\(\implies\) I = x \(cot^{-1}x\) – \(log |{1\over \sqrt{ 1+ x^2}}|\) + C

Hence, \(\int\) \(cot^{-1}x\) dx = \(xcot^{-1}x\) + \(1\over 2\) \(log |1 + x^2|\) + C

Example : Evaluate \(\int\) \(x cot^{-1} x\) dx

Solution : We have,

I = \(\int\)  \(x cot^{-1} x\) dx

By using integration by parts formula,

I = \(cot^{-1} x\) \(x^2\over 2\) – \(\int\) \(-1\over 1 + x^2\) \(\times\) \(x^2\over 2\) dx

I = \(tan^{-1} x\) \(x^2\over 2\) + \(1\over 2\) \(\int\) \(x^2 + 1 – 1\over 1 + x^2\)dx

= \(x^2\over 2\) \(cot^{-1} x\) + \(1\over 2\) \(\int\)  1 – \(1\over 1 + x^2\)dx

\(\implies\) I = \(x^2\over 2\) \(cot^{-1} x\) + \(1\over 2\) (x  – \(tan^{-1} x\)) + C

\(\implies\) I = \(x^2\over 2\) \(cot^{-1} x\) + \(x\over 2\) – \(tan^{-1} x\over 2\) + C


Related Questions

What is the Differentiation of cot inverse x ?

What is the Integration of Cotx ?

What is the integration of sec inverse root x ?

Leave a Comment

Your email address will not be published.